The Urgency of the Education Cultural Program in Increasing Competitiveness in MAN 1 and 4 Jombang - Fathur Rochim (Yayasan Indonesia Emerging Literacy Education, 2023)
The Urgency of Education Culture is indeed a barometer of Madrasah activities which is a measure of whether the Madrasah has a culture that activities which is a measure of whether the Madrasah has a culture that produces a good result for the Madrasah or vice versa a bad culture for the etis. Madrasah, therefore MAN 1 and 4 Jombang prioritize Education Culture in increasing the power the competitiveness of the institution so that the institution has good icons and habits in the daily life of the madrasa so as to increase the competitiveness of the madrasa. the purpose of this research is to find and analyze the Madrasah cultural program in increasing competitiveness. This study uses a qualitative approach with a multi-site study design. Data collection in this study used in-depth interviews, observation, and documentation techniques in which the data sources were people, documents (papers) and places (place). The results of this study fully strengthen the theory of the Culture of a School conveyed by strengthening the theories of Beare, Caldwell, Spinks and Milikan that the main principle in Education Culture is the Madrasah Cultural Program which contains goals and objectives (Aims and objectives), Curriculum (Curriculum), language (Language), Thought (Metaphor) and Organizing (Organizational).